Does surgical delay for radical prostatectomy affect patient pathological outcome? A retrospective analysis from a Canadian cohort - Zanaty, Marc (Can Urol Assoc J, 2017)
INTRODUCTION: We sought to assess the impact of surgical wait time (SWT) to robot-assisted radical prostatectomy (RARP) on final pathological outcome. METHODS: A retrospective review of RARP patient records operated between 2006 and 2015 was conducted. SWT was defined as period from prostate biopsy to surgery. Primary outcome was the impact on postoperative Cancer of the Prostate Risk Assessment (CAPRA-S) score. Patients were stratified according to D’Amico risk categories. Univariate analysis (UVA) and multivariable (MVA) analysis with a generalized linear model was used to evaluate the effect of SWT and other predictive factors on pathological outcome in individual risk group and on the overall sample. RESULTS: A total of 835 patients were eligible for analysis. Mean SWT was significantly different between the three D’Amico groups, with mean SWT of 180.22 days (95% confidence interval [CI] 169.03; 191.41), 159.14 days (95% CI 152.38; 165.90), and 138.96 days (95% CI 124.60; 153.33) for low-, intermediate-, and high-risk groups, respectively (p<0.001). After stratification by D’Amico risk group, no significant association was observed between SWT and CAPRA-S score in the three risk categories on UVA and MVA. Predictors of higher CAPRA-S score in the multivariable model in the overall cohort were: older age (p=0.014), biopsy Gleason score (p<0.001), percentage of positive cores (p<0.001), and clinical stage (p<0.001). CONCLUSIONS: In the present study evaluating SWT for RARP in a Canadian socialized system, increased delay for surgery does not appear to impact the pathological outcome. Further studies are required to evaluate the impact of wait time on biochemical recurrence-free survival, cancer-specific survival, and overall survival.